Penggunaan Media Pembelajaran Audiovisual dalam Meningkatkan Hasil Belajar Siswa di SMP Katolik Santa Bernadeth Kembes - Bernadina Waha Labuan; Hadi Ignatius Untu (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2025)
The purpose of this study was to find out the reality of the use of learning media in improving student learning outcomes at Santa Bernadeth Kembes Catholic Junior High School and the supporting and inhibiting factors for the use of audiovisual learning media in improving student learning outcomes and efforts to use audiovisual learning media in improving student learning outcomes. technique/type of descriptive research with a qualitative approach. Data collection techniques used in qualitative research are Observation, Interview and Documentation. In this study, the main instrument is the author himself. The conclusion of the study consists of three parts. First: teachers realize that the use of audiovisual learning media is very important, but because of the obstacles that exist from teachers and students so that the use of audiovisual learning media is not optimal. second: Factors supporting the use of audiovisual learning media in improving student learning outcomes at Santa Bernadeth Kembes Catholic Junior High School, namely by utilizing the internet and the Whatsapp application so that teaching and learning activities continue. third: Efforts to use audiovisual learning media in improving student learning outcomes at Santa Bernadeth Kembes Catholic Junior High School, namely by utilizing existing supporting media in schools in the form of printed books so that teaching and learning activities continue.